Autophagy in immunity against mycobacterium tuberculosis: a model system to dissect immunological roles of autophagy - Deretic, Vojo; Delgado, Monica; Vergne, Isabelle; Master, Sharon; De Haro, Sergio; Ponpuak, Marisa; Singh, Sudha (Current topics in microbiology and immunology, 2009)
The recognition of autophagy as an immune mechanism has been affirmed in recent years. One of the model systems that has helped in the development of our current understanding of how autophagy and more traditional immunity systems cooperate in defense against intracellular pathogens is macrophage infection with Mycobacterium tuberculosis. M. tuberculosis is a highly significant human pathogen that latently infects billions of people and causes active disease in millions of patients worldwide. The ability of the tubercle bacillus to persist in human populations rests upon its macrophage parasitism. One of the initial reports on the ability of autophagy to act as a cell-autonomous innate immunity mechanism capable of eliminating intracellular bacteria was on M. tuberculosis. This model system has further contributed to the recognition of multiple connections between conventional immune regulators and autophagy. In this chapter, we will review how these studies have helped to establish the following principles: (1) autophagy functions as an innate defense mechanism against intracellular microbes; (2) autophagy is under the control of pattern recognition receptors (PRR) such as Toll-like receptors (TLR), and it acts as one of the immunological output effectors of PRR and TLR signaling; (3) autophagy is one of the effector functions associated with the immunity-regulated GTPases, which were initially characterized as molecules involved in cell-autonomous defense, but whose mechanism of function was unknown until recently; (4) autophagy is an immune effector of Th1/Th2 T cell response polarization-autophagy is activated by Th1 cytokines (which act in defense against intracellular pathogens) and is inhibited by Th2 cytokines (which make cells accessible to intracellular pathogens). Collectively, the studies employing the M. tuberculosis autophagy model system have contributed to the development of a more comprehensive view of autophagy as an immunological process. This work and related studies by others have led us to propose a model of how autophagy, an ancient innate immunity defense, became integrated over the course of evolution with other immune mechanisms of ever-increasing complexity.